Constraints Hindering Adoption of ICT in Government Secondary Schools in Tanzania: The Case of Hanang District - Kweka, Kunda Humphrey; Ndibalema, Placidius (International Journal of Educational Technology and Learning, 2018)
This paper addresses teachers’ skills on ICT Integration in teaching and learning and constraints that hinder the adoption in Government owned secondary schools. The study employed a cross-section research design which guided the collection of both quantitative and qualitative data. Simple random sampling was employed in the selection of participants of which data were collected from 75 teachers in government secondary schools, 15 Heads of Schools, 1 DEO and 3 Quality Assurers. Questionnaires and interviews were used to obtain data. Qualitative data were analysed through content analysis while descriptive statistics was used to analyse quantitative data with the aid of SPSS version 21. The findings revealed that, most of the secondary school teachers had minimal skills of integrating ICT in teaching and learning due to different challenges such as lack of ICT facilities, inadequate computer labs in schools, and inadequate pre-service and in-service teachers training. Finally, the paper recommends a holistic approach in harmonising the curriculum requirements and the ICT policy strategies so as to create awareness among teachers, thus develop the required ICT pedagogical skills.